2011
DOI: 10.1186/1471-2180-11-193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stool microbiota signatures in two cohorts of Asian (Singapore and Indonesia) newborns at risk of atopy

Abstract: BackgroundStudies have suggested that demographic and lifestyle factors could shape the composition of fecal microbiota in early life. This study evaluated infant stool microbiota signatures in two Asian populations, Singapore (n = 42) and Indonesia (n = 32) with contrasting socioeconomic development, and examined the putative influences of demographic factors on these human fecal associated bacterial signatures.ResultsLongitudinal analysis showed associations of geographical origin with Clostridium leptum, At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 51 publications
7
35
2
Order By: Relevance
“…antibiotic use in infancy) while being mindful of the relatively small number of subjects within microbiota profiles. These variables were chosen based on clinical plausibility and a priori knowledge . In the sensitivity analysis, we repeated the multivariable model with the number of siblings as the ordinal variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…antibiotic use in infancy) while being mindful of the relatively small number of subjects within microbiota profiles. These variables were chosen based on clinical plausibility and a priori knowledge . In the sensitivity analysis, we repeated the multivariable model with the number of siblings as the ordinal variable.…”
Section: Methodsmentioning
confidence: 99%
“…To date, most microbiome research has focused on the gut, and, with regard to the previous comments, the possible link between the presence of older siblings and specific fecal microbiota . The airway, however, is a major portal for microbial exposure, and the airway microbiota has been found to influence immune response in patients with asthma .…”
mentioning
confidence: 99%
“…Indeed, several lines of evidence have shown that intestinal dysbiosis (imbalance of microbiota) is a feature of chronic disease as well as diet. Population differences in microbiota composition are well known; the profiles of gut bacteria in American, European, and Asian cohorts are quantifiably different [5254]. Furthermore, gut microbiota is altered in allergic diseases and other chronic inflammatory disorders such as Crohn's disease [55].…”
Section: Gut Microbiota Short-chain Fatty Acids and Healthmentioning
confidence: 99%
“…Moreover, the presence of pathogenic species, or absence of beneficial species, in early childhood has been suggested to play a key role in the initiation of preterm birth [12], development of asthma or eczema [13], [14], allergy [15], autism [16] or other immunological deficiency [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the growing recognition that commensal microbes may contribute fundamentally to infant and childhood development and immunity [14], [15], [17], [18], [28], [29], only a few studies have determined the microbial composition of the first intestinal discharge, or meconium, in premature [30][32] and in term neonates [24], [25] and linked its bacterial content to maternal eczema and infant mucus congestion during the first year of life [24]. Therefore, the main objectives of this study were to further characterize the composition of the meconium and assess whether maternal diabetes status, prior to or during pregnancy, affects bacterial composition of the newborn's first stool.…”
Section: Introductionmentioning
confidence: 99%